2019
DOI: 10.3390/cells8091002
|View full text |Cite
|
Sign up to set email alerts
|

Protein S100-A7 Derived from Digested Dentin Is a Critical Molecule for Dentin Pulp Regeneration

Abstract: Dentin consists of inorganic hard tissue and organic dentin matrix components (DMCs). Various kinds of bioactive molecules are included in DMCs and some of them can be released after digestion by endogenous matrix metalloproteinases (MMPs) in the caries region. Digested DMCs induced by MMP20 have been reported to promote pulpal wound healing processes, but the released critical molecules responsible for this phenomenon are unclear. Here, we identified protein S100-A7 as a critical molecule for pulpal healing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…A heat map of the key transcripts for the osteo/dentinogenic differentiation process is shown in Figure 6E. These genes were consistent with those related to osteo/dentinogenic differentiation that were identified in previous reports [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Rna Sequence Analysissupporting
confidence: 87%
“…A heat map of the key transcripts for the osteo/dentinogenic differentiation process is shown in Figure 6E. These genes were consistent with those related to osteo/dentinogenic differentiation that were identified in previous reports [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Rna Sequence Analysissupporting
confidence: 87%
“…dECM biomaterials undergo proteolytic digestion once implanted and several studies have shown that chemical or enzymatic breakdown of dECM biomaterials produces novel or hidden cryptic ECM molecules and can modify the biological properties of dECMs [ 46 49 ], including the recruitment of MSCs [ 40 ]. For example, protein S100-A7 derived from MMP-20 digested dentin matrix was shown to recruit CD146 positive cells to the site of wounded dental pulp in a rat model [ 50 ]. A collagen III-derived peptide isolated from a dECM by proteolytic degradation was shown to be chemotactic towards human cortical neural stem cells, adipocyte stem cells, myoblast cells and Schwann cells in vitro and in vivo [ 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that matrix metalloproteinase-20 digested organic dentin matrix components (DMCs) promoted tertiary dentin formation ( Okamoto et al 2018 ). Moreover, proteome analysis of the digested DMCs revealed that protein S100A7 (S100A7) and S100A8 promoted pulpal wound healing ( McLachlan et al 2004 ; Komichi et al 2019 ). S100A7 and S100A8 are both present in dentin and pulp; they promoted tertiary dentin formation in a rat DPC model ( Komichi et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%